2018
DOI: 10.1080/15389588.2018.1453134
|View full text |Cite
|
Sign up to set email alerts
|

Investigating factors influencing drivers' speed selection behavior under reduced visibility conditions

Abstract: Driving ability is directly associated with speed selection in reduced visibility conditions, and some demographic data indirectly influence speed selection. This study provides useful recommendations for drivers' training programs to reduce casualties from accidents in low-visibility conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…In this study, a mixed logit model (MXL) is used to predict the probability of the three driverinjury severity outcomes at highway-rail grade crossing accidents reported by police to estimate discrete driver-injury severity outcomes [32,33],…”
Section: Mixed Logit Modelmentioning
confidence: 99%
“…In this study, a mixed logit model (MXL) is used to predict the probability of the three driverinjury severity outcomes at highway-rail grade crossing accidents reported by police to estimate discrete driver-injury severity outcomes [32,33],…”
Section: Mixed Logit Modelmentioning
confidence: 99%
“…To conform to the model logic, according to the MI of Model 1, the corresponding path was increased from large to small, and the modified Model 2 was obtained. The fitting results are shown in Table 5, which indicate that the fitting degree of Model 2 is acceptable (Zhang et al, 2018;Wang et al, 2019). The drivers' SA influential factors path relationship is shown in Figure 4 for Models 1 and 2.…”
Section: Performance Of Different Modelsmentioning
confidence: 83%
“…While existing research as to the role of gender in promoting SA is mixed, with some studies finding that gender did not have a significant impact on SA in various driving scenarios (Heenan et al, 2014), some studies have found that gender could result in significant differences in driving behavior (Machin and Sankey, 2008;Zhang et al, 2018;Wang et al, 2019). This factor requires further investigation.…”
Section: Proposed Methodology Factors Affecting Situation Awarenessmentioning
confidence: 97%
“…The corresponding odds ratios are 2.57 during dark hours with street lighting, and 4.61 during dusk or dawn conditions. Since speed selection behavior of drivers in reduced visibility changes with their varying driving ability, the vehicle's speed is not always within a safe range, which contributes to the increment in the fatality risk [41].…”
Section: Basic Modelmentioning
confidence: 99%